MICROTECTONICAL ANALYSIS OF PORPHYRIC GRANITES OF NORTH-WESTERN PART OF UKRAINIAN SHIELD - PAVLOV, G.; PAVLOVA, O.; BUBNOVA, O.; FILIPOV, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
According to the microtectonical analysis results the periods of structural-tectonic evolution of megacrystic granites of the North- Western region of the Ukrainian shield have been determined. The mineral paragenesises which occur on each stage of magmatic reworking are distinguished and described here. An influence of hydrothermal-metasomatic infiltrating solutions on the mineral composition of the rocks on all stages of tectogenesis has been discovered.